(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2026)
This study explores how Artificial Intelligence (AI) can be used to improve clean cooking energy technologies in Tanzania, particularly in enhancing system performance and supporting access to carbon credit markets. The research is based on a critical review and comparison of existing studies and real-world applications of AI in technologies such as improved biomass stoves, biogas systems, and electric cooking devices. It focuses on key AI functions, including real-time monitoring, predictive maintenance, user behavior analysis, and digital systems for measurement, reporting, and verification (MRV). The results show that AI can make a practical difference in how these technologies operate. For example, real-time monitoring helps improve fuel efficiency and reduce emissions by optimizing how stoves are used. Predictive maintenance reduces breakdowns and extends the lifespan of equipment, while analysis of user behavior provides insights that can help reduce the common practice of using multiple fuels (fuel stacking). In addition, AI-based MRV systems improve the accuracy and transparency of carbon credit verification by automating data collection and identifying irregularities. Overall, the study finds that AI is not only a promising concept but a practical tool that can improve efficiency, reduce emissions, and strengthen carbon accounting systems. However, challenges such as limited digital infrastructure, high costs, and lack of technical expertise may slow down its largescale adoption in Tanzania. This paper contributes by bringing together existing knowledge and presenting a clear, Tanzaniafocused perspective on how AI can support the growth of clean cooking technologies and access to climate finance.